2004
DOI: 10.1017/s1461145704004626
|View full text |Cite
|
Sign up to set email alerts
|

Does comorbid subthreshold anxiety affect clinical presentation and treatment response in depression? A preliminary 12-month naturalistic study

Abstract: The aim of this study was to evaluate the effects of comorbid subthreshold anxiety on the course and the treatment of Depressive Disorders. The sample studied comprised four groups defined by the DSM-IV Axis I diagnosis: (1) Patients with a Major Depressive Disorder (MDD) and an Anxiety Disorder (DA); (2) patients with MDD and a subthreshold Anxiety Disorder (Da); (3) patients with subthreshold depression and an Anxiety Disorder (dA); (4) patients with subthreshold depression and subthreshold anxiety (da). HAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Anxious depression was associated with poorer acute outcomes than nonanxious depression, and remission was significantly less likely to occur among these patients . In another Level‐2 study, patients with depression and a subthreshold anxiety disorder showed an overall worse response to antidepressants, with a longer latency and less reduction of symptoms …”
Section: Resultsmentioning
confidence: 99%
“…Anxious depression was associated with poorer acute outcomes than nonanxious depression, and remission was significantly less likely to occur among these patients . In another Level‐2 study, patients with depression and a subthreshold anxiety disorder showed an overall worse response to antidepressants, with a longer latency and less reduction of symptoms …”
Section: Resultsmentioning
confidence: 99%
“…The nature and cause of poor medication adherence have been primarily linked to a high incidence of medication-related adverse events, which is also one of the main reasons for a change in therapy (10,28,29). A possible explanation for this finding may be that patients with comorbid anxiety and depression commonly have more severe symptoms and a poorer outcome than patients without comorbid depression and may thus require more aggressive treatment (30,31). A possible explanation for this finding may be that patients with comorbid anxiety and depression commonly have more severe symptoms and a poorer outcome than patients without comorbid depression and may thus require more aggressive treatment (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The large, multi‐center Sequenced Treatment Alternatives to Relieve Depression study (STAR*D) found that demographically, individuals with anxious depression are more likely to be older, unemployed, and less educated . Furthermore, some studies have shown that those with anxious depression have poorer response to antidepressants, including significantly lower response and remission rates, more frequent and intense side effects, and more serious adverse events, despite medication changes or augmentation techniques …”
Section: Introductionmentioning
confidence: 93%